Which Proteins? The Challenge of Identifying the Protective Antigens for Next-Generation Capripoxvirus Vaccines - Mahder Teffera; Hani Boshra; Timothy R. Bowden; Shawn Babiuk (Vaccines)
Sheeppox, goatpox, and lumpy skin disease continue to negatively impact the sheep, goat, and cattle industries in countries where these diseases are present and threaten to spread into new regions. Effective vaccines are available for disease control and eradication. However, commercial vaccines are based on live attenuated virus isolates and therefore it is not currently possible to differentiate between infected and vaccinated animals (DIVA), which severely limits the use of these vaccines in countries that are free from disease and at risk of an incursion. The development of next-generation vaccines, including recombinant protein, viral-vectored, and mRNA, has been limited due to the lack of understanding of the protective antigen(s) of capripoxviruses. The complexity of capripoxviruses, with up to 156 open reading frames, makes the identification of protective antigen(s) difficult. This paper identifies the most promising antigens by first considering the membrane-associated proteins and then further selecting proteins based on immunogenicity and their role in immunity by comparing them to known orthopoxvirus homologues. From the 156 potential antigens, 13 have been identified as being the most likely to be protective. Further evaluation of these proteins, as immunogens, would be required to identify the optimal combination of immunodominant antigen(s) for the development of next-generation capripoxvirus vaccines.